Perceptions and Degree of Satisfaction with the Health Sciences University Educational Community Regarding the Measures Adopted for the Prevention of COVID-19 in the Academic Year 2020/2021 - Óscar Rodríguez-Nogueira; Raquel Leirós-Rodríguez; Enedina Quiroga-Sánchez; Mª José Álvarez-Álvarez; Lorena Álvarez-Barrio (MDPI AG, 2021)
The COVID-19 pandemic caused the start of the academic year 2020/2021 to be conditioned by health and safety regulations. The present research was defined with the aim of analyzing the degree of satisfaction and perceptions on the establishment of bubble groups and pairs and on the use of audiovisual platforms for the development of theoretical and practical university teaching in three degrees of health sciences. A cross-sectional descriptive study was carried out on a representative sample of students and teachers of health sciences in Ponferrada (n = 285). Specific questionnaires designed for this study were completed virtually during April and May 2021. The results indicate that that satisfaction was moderate-high. The perception of the influence of bubble pairs on the quality of teaching can be interpreted as very low. These results increase with the age and academic and professional experience of students and faculty members, respectively. However, the participants belonging to physiotherapy considered that the quality of teaching had worsened much more compared to their counterparts in nursing and podiatry.